Superior performances of in situ synthesized ZnO/PVDF thin film based self-poled piezoelectric nanogenerator and self-charged photo-power bank with high durability. (February 2018) - Thakur, Pradip; Kool, Arpan; Hoque, Nur Amin; Bagchi, Biswajoy; Khatun, Farha; Biswas, Prosenjit; Brahma, Debdip; Roy, Swagata; Banerjee, Somtirtha; Das, Sukhen
Abstract: Herein, we have synthesized multitalented β crystallite prosperous and high dielectric ZnO/PVDF thin films via in situ process for energy harvesting and energy storing applications. The impregnation of the ZnO nanoparticles (NPs) in PVDF matrix has enhanced the electroactive β crystal nucleation ( F(β) 84% at 0.85 vol% doping) as well as piezoelectricity (d33 50 pC/N at 50 Hz) and the dielectric value ( 109 at 1.7 vol% loading) effectively. The nanogenerator, named as ZPENG and the self-charged photo-power bank (PPB) developed using the optimized supercilious piezoelectric and dielectric films have exhibited superiority in power generation (power density 32.5 mW/cm 3 ) and energy storage capability ( 2000 F/) respectively that are highly impressive outputs compare to other similar prototype devices reported elsewhere till now. The realistic utilities of our fabricated ZPENG have been proved by light up 15 serially connected commercial blue light emitting diodes (LEDs) and charging capacitor (1 μF) in a small time span under repetitive finger impartation. The ZPENG is also shows continuous band like power generation under vibration occurred due to blood circulation in human body. The self-charged PPB is also able to power up blue LED that has confirmed its realistic applicability as a power source. Graphical abstract: Highlights: Fabrication of two simple ZnO-PVDF film based prototype energy harvesting unit. The nanogenerator (ZPENG) reveals to a remarkable power density 32.5 mW/cm 3 . The photo-power bank with storage capability of 2000 F/m 2 with maximum power density of 3.04 W/m 2 . The ZPENG and PPB shows excellent power creation capability over a long periods.